Smart agriculture for crop disease management - Ahmad Radzi, Syafeeza; Mohd Saad, Wira Hidayat (Penerbit UTeM Press, 2025)
Unlock the future of farming with "Smart Agriculture for Crop Disease Management," a revolutionary guide that bridges the traditional farming techniques with cutting-edge technology. Dive into this comprehensive book and discover a mobile-based solution designed to intelligently diagnose and treat diseases plaguing solanaceous crops, empowering farmers to reduce yield losses and enhance crop health. Immerse yourself in the world of visual imaging and deep learning models, where a user-friendly mobile application becomes your assistant in identifying and diagnosing various crop diseases. Learn how this innovative technology helps prevent the misuse of fertilizers and preserves essential soil microorganisms. Uncover the critical importance of Solanaceous crops and the transformative power of mobile-based solutions in modern agriculture. Gain invaluable insights into creating accurate datasets and harnessing Al for efficient disease detection. This book offers a step-by-step guide on developing the mobile app, providing practical advice on building, integrating, and deploying the solution for maximum effectiveness in real-world conditions. "Smart Agriculture for Crop Disease Management" is more than a guide; it's a blueprint for sustainable agriculture. Equip yourself with the tools to embrace modern technology and achieve unprecedented success in your fields.